Pentingnya Ilmu Manajemen Dalam Pandangan Islam - Lita Saydina; Eky Tiasriski; Nabilla Habibillah; Az Zahra Putri Setyo Wati; Yayat Suharyat (LPPM Politeknik Pratama, 2023)
The purpose of this study is to study management science in an Islamic perspective. This research method uses qualitative research design and conducts data collection techniques using literature review methods with secondary data from previous research and other available sources. On the other hand, technical data analysis is carried out by drawing conclusions. So that the result that can be concluded is the management of a very important aspect in Muslims. . Islam provides clear guidelines and principles that can be applied in management practice. Good and effective management is a must in the context of Islam. Islam encourages its Ummah to manage resources and time wisely, and to apply the principles of ethics and justice in all aspects of life, including in the field of management.